Court Conspiracy In Capitalistic Society In John Girsham's The Runaway Jury (1996): A Marxist Criticism - Raharjo, Dodi Bangun; , Dr. M. Thoyibi, M.S; , Mauly Halwat Hikmat, Ph. D (2014)
This research aims at analyzing court conspiracy in capitalistic society in John Girsham's The Runaway Jury by using Marxist Criticism. The major problem in this research is how court conspiracy is reflected in John Girsham's The Runaway Jury. The research consists of two objectives: analyzing the novel based on structural elements and analyzing the novel based on Marxist Criticism. This study uses qualitative research. The object of the study is The Runaway Jury novel written by John Girsham. There are two kinds of data source: primary and secondary. The primary data source is the text of the novel John Girsham's The Runaway Jury and the secondary data sources are some books and article related to the subject. The method of collecting data in the research is library research by summarizing, paraphrasing, and documenting the data. In analyzing the data, the writer applies descriptive analysis. The results of the research are as follows. First, based on structural analysis, it is apparent that this novel contains a moral mesage that sometimes the trial is not always fair; the upper class can set the law because the law can be purchased. Second, based on Marxist analysis, this novel depicts the struggle of bribes and threat.